Voice over internet protocol (VoIP) i Talk Technology / Latifah Mohd. Yusoff - Mohd. Yusoff, Latifah (2002)
Voice Over IP (VoIP) is a technology that allows telephone calls to be transmitted over data networks such as the internet. It is an alternative to the traditional Public Switch Telephone Network (PSTN) based telephony. Implementing this technology can result in drastic savings on the costs of long distance phone calls. This paper present the concept of VoIP and its applications. The actual VoIP network diagram , call processing, call flow and call routing based on the i Talk Technology (product of Telecom Malaysia Bhd.) being analyzed. Data samples were taken from PSTN node as well as IP "node to measure traffic call and analysis on performance of the i Talk prepaid call by various area such as traffic intensity, type of call, status of the telephone call successful or otherwise or some other reason are made. Simulation of the sample data was done using visual basic software and Excel 2000. Problems on Quality of Service (QOS) such as scalability, packet loss, delays, congestions are analyzed and solutions are proposed.